(3OQI GdCSdGc aj JGQjN OhdI GdCJQGcs - (3GdMSf Hf YeQ Hf GdMSf Hf MHjH, CHh eMeO, HOQ GdOjf GdMdHj,J (B779 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJGQjN dCRdjJg hbOeg hHYO agPg ChQGb JTJed Ydi OQI GdCSdGc SfI NeS YTQI hSHYeFI s
(3BNQgG (B:s
(3haGI Jbi GdOjf Hf GdVQjQ ef MhGOK SfI (B761 s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B206 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B169s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(34(3L(B) s
Keywords: (3GdJGQjNs